Precision production technology for jasmine - Sundar, S T Bini; Kannan, M; Jawaharlal, M (Indian Horticulture, 2018)
Jasmine is an important commercial loose flower crop. A precision production technology has been developed at TNAU, Coimbatore, to increase its production, productivity and net income of growers. The technology involves, intensive field preparation, precise spacing, enriched media consortia, application of fertilizers through drip and fertigation system, spraying of biostimulants and micronutrients, and integrated pest and disease management practices. Adoption of the technology results in 65% increase in flower yield.